Religion and the exercise of public authority - Berger, Benjamin L.; Moon, Richard (Hart Publishing, 2016)
The meaning and entailment of the religious neutrality of the state : the case of public employees / Jocelyn Maclure -- Against circumspection : judges, religious symbols, and signs of moral independence / Benjamin L Berger -- Religious lawyering and legal ethics / Faisal Bhabha -- Managing and imagining religion in Canada from the top and the bottom : 15 years after / Paul Bramadat -- God keep our land : the legal ritual of the McKenna-McBride Royal Commission, 1913-16 / Pamela E Klassen -- In/visible religion in public institutions : Canadian Muslim public servants / Amélie Barras, Jennifer A Selby, and Lori G Beaman -- The prayer case saga in Canada : an expert insider? : perspective on praying in the political and public arenas / Solange Lefebvre -- Physicians' rights to conscientious objection / Bruce Ryder -- Conscientious objections by civil servants : the case of marriage commissioners and same-sex civil marriages / Richard Moon -- A freedom of religion-based argument against religious schools / Daniel M Weinstock -- "Open house/portes ouvertes" : classrooms as sites of interfaith interface / Shauna Van Praagh